The effects of LASPO on court efficiency and the impact of litigants in person: an empirical study - Kalliris, Konstantinos; Alysandratos, Theodore (SSRN, 2022)
In this article, we examine the effects of LASPO on measures of court efficiency. We focus on family law, since LASPO kept public family law proceedings in its scope but made almost the entirety of private family law unavailable for legal aid. We find an increase in the number of Litigants in Person and evidence that people continued to go to court, despite the lack of legal counsel. We also find a drop in the efficiency of family courts. We attribute LASPO’s adverse effect on court efficiency to the impact of self-representation on court proceedings. Specifically, we discuss how cuts to legal aid not only increased self-representation but created a new type of Litigant in Person. Most Litigants in Person post-LASPO are less capable of representing themselves and defending their interests in court, due to a lack of understanding of the law and procedural rules. Given the low levels of successful mediation, this new reality creates more work for judges, lawyers and administrators, forcing the judicial system to commit more resources to litigation. We conclude that LASPO failed to deliver on its promise to lighten the workload of family courts and make them better value for money for the taxpayer
Nach Informationen von SSRN wurde die ursprüngliche Fassung des Dokuments August 21, 2022 erstellt
Gesehen am 05.05.2023